Factors of Early-Stage Entrepreneurial Aspirations in Asia Pacific Economies - Huynh, Nhan; Dao, Anh (Journal of Asian Business Strategy, 2021)
This paper directly explores of the determinants of growth aspirations for the early-stage entrepreneurs in Asia Pacific economies. By studying the relationship between five orientations of the early-stage entrepreneurs and their growth aspirations, this study can provide a comprehensive understanding to stimulate the entrepreneurial activities in examined countries. The data source is extracted from a sample of firms in 14 Asia Pacific economies participated in the 2015 Global Entrepreneurship Monitor Adult Population Survey. This study employs the binary logistic regression with a dummy variable of country orientations. The results demonstrate no significant relationship between innovative orientation, entrepreneurial probability and the firms’ growth aspirations. The updated technology and new product or service implementations can neither deteriorate nor stimulate the early-stage entrepreneurial companies’ growth aspirations in Asia Pacific countries. The relations of international orientation, increase-income motivation and high-risk aversion with growth aspirations are significantly negative. This denotes an adverse influence of the internationalisation and the income growth expectations, and frustration to the Asia Pacific firms’ growth aspirations. The results also indicate that firms from factor-driven and efficiency-driven economies have fewer growth aspirations than those from innovation-driven countries. Although having some limitations, this study sheds light on the entrepreneurship understanding of policymakers, academics and professional businesspersons.